Espectroscopia Raman de cristais de DL-norleucina em altas pressões - Silva, Rômulo Sampaio da (2022)
Amino acids are the basic building blocks of proteins, which are indispensable for life. In the solid state, the stability of the structure is mainly maintained by hydrogen bonding that occurs between the nitrogen of the amino group and the oxygen of the carboxylic group. Mainly due to the versatility of their structures, amino acids can form polymorphic structures, bind to other amino acids forming dipeptides or even to other molecules and atoms such as: metals, organic and inorganic molecules, forming salts and metallics creating new materials with properties different from those of pure amino acids and even in some cases with potential technological applications mainly non-linear optical properties with potential applicability in electronic devices and pharmaceutical industry. Numerous works have been described in the study of the stability of the structure of amino acids both as a function of pressure and temperature. Several phase transitions have been reported. In this work we present a study by Raman spectroscopy of the DL-norleucine crystal as a function of the hydrostatic pressure varying from ambient pressure to 2.87 GPa. During the compression process, changes were observed in the behavior of the vibrational modes that raise suspicion of two possible conformational transitions around 0.67 GPa and 2.09 GPa. This work also presents an analysis of the vibrational modes as a function of temperature, where Raman spectroscopy measurements were performed in the range from 13 to 295 K. During the cooling process, changes were observed that suggest two possible phase transitions at 175 and 70 K.